Der polnische Weg zum Kapitalismus - Tittenbrun, Jacek (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1992)
Tue governmental strategy of rapid privatization by weakening the state sector has failed: the state owned firms were driven towards bankruptcy, the private firms towards an illegal black economy. Tue social costs of the transformation are enormous, people became frustrated but external constraints force Poland to integrale into the capitalist world system.